PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Arif Darmawan (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
This study aims to examine whether there is an influence of organizational culture, leadership, work environment and work discipline on employee performance. This research is a causality research design with as many as 67 people as a sample who are employees of PT Citra Buana Prakarsa. The sampling method used was saturated sampling technique with a population of 67 people. The data analysis method used is multiple linear regression analysis method using the SPSS (Statistical Package for the Social Sciences) program version 25. The results of the test show that organizational culture has no effect on employee performance, while leadership, work environment and work discipline have a significant effect on employee performance. employee performance.